Acuerdos internacionales relacionados con las migraciones - Maúrtua de Romaña, Oscar (2018)
Perú is part of various treaties, at a global, regional and bilateral level, which generate specific obligations to the migrant population. Although there is a regulation related to the human rights of migrants, every migrant who arrives in a country must respect national laws. In this article we deal with the international agreements and conventions that are incumbent upon the Peruvian State to take into account.